The Clinical Pregnancy and Live Birth Following Transfer of One Arrested Embryo: A Case Report - Ghafarizade, Ali Asghar; Shojafar, Elham; Naderi, Samira; Seifi, Fatemeh; Noshad, Alireza; Lavasani, Zohreh; Noshad, Alireza; Kalhori, Zahra; Ghadiri, Elahe (Clinical Journal of Obstetrics and Gynecology, 2024)
Background: One of the problems in vitro fertilization (IVF) treatment for infertility is the high frequency of embryo developmental arrest in the preimplantation stages. Arrested embryos were not selected for transfer and were usually discarded. Case report: We present a case of clinical pregnancy and live birth following IVF treatment and transfer of one arrested embryo. A 31-year-old woman with unexplained infertility underwent IVF treatment. Using the IVF procedure, 7 embryos were produced which were frozen on day 3. In order to embryo transfer in the blastocyst stage, two embryos were thawed and cultured for 2 days. After thawing, one of them was not suitable for transfer and another embryo was arrested at the 10-12 cell stage. Discussion: The Clinical pregnancy and live birth happened after the transfer of an arrested embryo on day 5. Conclusion: This case showed that arrested embryos may resume growth after the transfer to the uterus and result in a successful pregnancy and live birth.